Virtual simulation of Lathe Machining Training Based on Unity3D. (September 2020) - Shen, Bin; Chen, Baoqi; Wang, Yanwu
Abstract: In this paper, through the use of SolidWorks three-dimensional software for the lathe three-dimensional modeling, the lathe three-dimensional model can more intuitively express the structure of the lathe. Through the analysis of the reducer shaft, this paper developed the machining process, and then the solid modeling of the shaft, and finally through the Unity3D software for the reducer shaft machining simulation analysis.